Beyond the Veil: Unravelling the Spectral Resonances of Trauma in Murakami’s Kafka on the Shore - Wajeeha Nabi Ahmed; Dr. Saima Bashir(Corresponding Author) (Scholar Insight Journal, 2026)
This study underscores the psychological exploration of hauntology in Murakami’s novel Kafka on the Shore. The objective of this research is to mirror the spectral reverberation of trauma that refuses to remain buried silently. Moreover, by following the theoretical frameworks of hauntology and Psychoanalysis, this study situates the novel within mystical realms where unheard echoes and traumas contribute to shaping one’s personality. This study employs qualitative analysis incorporating close reading and thematic interpretation. Aforementioned, approach allows for profound comprehension of ways in which Murakami’s novel reevoke haunting space, thus echoing the unheard and unseen. Through revealing spectral undertones, this study justifies the narrative power as a dual force for illuminating the hidden recesses of human persona. Though this study paves the way to unravel the spectral essences underlying human psyche, however, the prospect of more compelling research in this direction is undeniable.